MoIVD-Mediated Leucine Catabolism Is Required for Vegetative Growth, Conidiation and Full Virulence of the Rice Blast Fungus Magnaporthe oryzae - Li, Ya; Zheng, Xiuxia; Zhu, Minghui; Chen, Mengting; Zhang, Shengnan; He, Fangyuan; Chen, Xiaomin; Lv, Jiarui; Pei, Mengtian; Zhang, Ye; Zhang, Yunhui; Wang, Wenzong; et al. (Frontiers in Microbiology, 2019)
Isovaleryl-CoA dehydrogenase (IVD), a member of the acyl-CoA dehydrogenase (ACAD) family, is a key enzyme catalyzing the conversion of isovaleryl-CoA to β-methylcrotonyl-CoA in the third reaction of the leucine catabolism pathway and simultaneously transferring electrons to the electron-transferring flavoprotein (ETF) for ATP synthesis. We previously identified the ETF ortholog in rice blast fungus Magnaporthe oryzae (MoETF) and showed that MoETF was essential for the fungal growth, conidiation and pathogenicity. To further investigate the biological function of electron-transferring proteins and clarify the role of leucine catabolism in growth and pathogenesis, we characterized MoIVD (M. oryzae isovaleryl-CoA dehydrogenase). MoIvd is highly conserved in fungi and its expression was highly induced by leucine. The Δmoivd mutants showed reduced growth, decreased conidiation and compromised pathogenicity, while the conidial germination and appressorial formation appeared normal. Consistent with a block in leucine degradation, the Δmoivd mutants accumulated isovaleric acid, and grew more slowly, fully lacked pigmentation and completely failed to produce conidia on leucine-rich medium. These defects were largely rescued by raising the extracellular pH, suggesting that the accumulation of isovaleric acid contributes to the growth and conidiation defects. However, the reduced virulence of the mutants was probably due to their inability to overcome oxidative stress, since a large amount of ROS (reactive oxygen species) accumulated in infected host cell. In addition, MoIvd is localized to mitochondria and interacted with its electron receptor MoEtfb, the β subunit of MoEtf. Taken together, our results suggest that MoIVD functions in leucine catabolism and is required for the vegetative growth, conidiation and full virulence of M. oryzae, providing the first evidence for IVD-mediated leucine catabolism in the development and pathogenesis of plant fungal pathogens.